Uncertainty Makes Me Emotional: Uncertainty as an Elicitor and Modulator of Emotional States - Morriss, Jayne; Tupitsa, Emma; Dodd, Helen F.; Hirsch, Colette R. (Frontiers in Psychology, 2022)
Uncertainty and emotion are an inevitable part of everyday life and play a vital role in mental health. Yet, our understanding of how uncertainty and emotion interact is limited. Here, an online survey was conducted (n = 231) to examine whether uncertainty evokes and modulates a range of negative and positive emotions. The data show that uncertainty is predominantly associated with negative emotional states such as fear/anxiety. However, uncertainty was also found to modulate a variety of other negative (i.e., sadness/upset, anger/frustration, and confusion) and positive (i.e., surprise/interest and excited/enthusiastic) emotional states, depending on the valence of an anticipated outcome (i.e., negative and positive) and the sub parameter of uncertainty (i.e., risk and ambiguity). Uncertainty increased the intensity of negative emotional states and decreased the intensity of positive emotional states. These findings support prior research suggesting that uncertainty is aversive and associated with negative emotional states such as fear and anxiety. However, the findings also revealed that uncertainty is involved in eliciting and modulating a wide array of emotional phenomena beyond fear and anxiety. This study highlights an opportunity for further study of how uncertainty and emotion interactions are conceptualised generally and in relation to mental health.